Diverse organization of voltage-gated calcium channels at presynaptic active zones - Zhang, Weijia; Jiang, He-Hai; Luo, Fujun (Frontiers in Synaptic Neuroscience, 2022)
Synapses are highly organized but are also highly diverse in their organization and properties to allow for optimizing the computing power of brain circuits. Along these lines, voltage-gated calcium (CaV) channels at the presynaptic active zone are heterogeneously organized, which creates a variety of calcium dynamics profiles that can shape neurotransmitter release properties of individual synapses. Extensive studies have revealed striking diversity in the subtype, number, and distribution of CaV channels, as well as the nanoscale topographic relationships to docked synaptic vesicles. Further, multi-protein complexes including RIMs, RIM-binding proteins, CAST/ELKS, and neurexins are required for coordinating the diverse organization of CaV channels at the presynaptic active zone. In this review, we highlight major advances in the studies of the functional organization of presynaptic CaV channels and discuss their physiological implications for synaptic transmission and short-term plasticity.